Sistema de innovación tecnológica para el fomento de la competitividad turística en el hotel Balandra - Farías Solórzano, Cira Xiomara (2021)
The objective of this study is to design a technological innovation system to promote tourist competitiveness at the Balandra hotel. The research is descriptive and explanatory with a qualitative approach. The investigative process consists of three phases, the first one focused on analyzing the elements and components associated with technological innovation in the hotel's operational areas. In this phase, instruments such as the interview, direct observation technical sheet, SWOT matrix and on-site visit were used. As a result, the hotel's technological investment was known, it has 403 technologies, tangible and intangible, also the technological needs of the establishment. Later, the technological innovation system was developed in relation to the dimensions and indicators of the Balandra hotel. For this, the dimensions and indicators were validated by applying the expert criteria expert method (Delphi). Finally, actions are proposed to promote competitive advantages associated with technological innovation in the Balandra hotel, for which the hotel's differentiating processes were identified in addition to the evaluation of competitive performance, the analysis of the competition and the determination of competitive advantages. Eight objectives are proposed with their respective actions for the improvement of the hotel's GTI, Likewise, a table was made with twelve control and feedback actions of the innovation system, this allows the efficient development of each of the processes that make up the hotel's technological innovation system.